2002
DOI: 10.1136/heart.88.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Intercoronary communication between the circumflex and right coronary arteries: distinct from coronary collaterals

Abstract: Objective: To determine the prevalence and correlates of lipid lowering drug use among older British men with established coronary heart disease (CHD). Design: Cross sectional survey within a cohort study (British regional heart study) carried out at 20 years of follow up in 1998-2000. Setting: General practices in 24 British towns. Participants: 3689 men aged 60-75 years (response rate 76%). Main outcome measures: Diagnoses of myocardial infarction and angina based on detailed review of general practice recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 2 publications
(4 reference statements)
1
12
0
2
Order By: Relevance
“…The contrast mixture used in our protocol differs from that recommended by the consensus conference [7] by the addition of blood [11]. We demonstrated that the addition of blood produces significantly more bubbles than saline and air alone, without affecting the sizes of the bubbles produced.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The contrast mixture used in our protocol differs from that recommended by the consensus conference [7] by the addition of blood [11]. We demonstrated that the addition of blood produces significantly more bubbles than saline and air alone, without affecting the sizes of the bubbles produced.…”
Section: Discussionmentioning
confidence: 63%
“…A negative test was one in which no microbubbles were detected within 20 s. A ‘significant’ v-aCS, consistent with the presence of a PFO, was defined as ≥15 microbubbles; this is based on our validation study of TCD versus TOE [11]. A ‘large’ v-aCS was defined as >50 microbubbles, and a ‘major’ shunt was defined as >50 microbubbles spontaneously or >10 microbubbles spontaneously with >80 following provocation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As comunicações intercoronárias têm a camada muscular bem desenvolvida, diâmetros superiores (≥ 1 mm), são extramurais e menos tortuosas, quando comparadas com as colaterais 10 .…”
Section: Discussionunclassified
“…Atak, et al reported one case among 7,986 angiograms. 4) Our case was the first among 12,674 angiograms performed during the last five years. In a postmortem study of 100 human hearts from individuals with an average age of 61 years, 7 cases of intercoronary artery were described.…”
Section: Casementioning
confidence: 99%